Social Determinants of Health and Health Literacy in Emergency Patients with Diabetic Ketoacidosis - Daniel F. Suarez; Ryan M. Schneider; Margo Girardi; Gina LaRossa; Julianne Yeary; Taylor Kaser; Rachel Ancona; Paulina Cruz Bravo; Richard T. Griffey (Western Journal of Emergency Medicine)
Introduction: Social determinants of health (SDoH) and health literacy have been demonstrated to significantly impact health outcomes. As part of a study of diabetic ketoacidosis (DKA) treatment from the emergency department (ED), we assessed the burden of SDoH and health literacy among patients with DKA to identify potentially modifiable risk factors in the development of DKA. Methods: This was an exploratory, prospective, cross-sectional study of adult patients with DKA in a large urban academic ED from March 2023–March 2024. We administered the Centers for Medicare & Medicaid Services Accountable Health Communities Health-Related Social Needs Screening Tool (SNST) and the Brief Health Literacy Screen (BHLS). Results: Of 126 identified ED patients with confirmed DKA, 57 completed the SNST and 72 completed the BHLS. Nearly all patients (56 patients, 98%) reported at least one unmet SDoH need, and 32 (56%) patients reported five or more. The most frequently reported SDoH needs were physical activity (77%), mental health (63%), financial strain (60%), substance use (54%), and food insecurity (51%). Seventy-two patients completed the BHLS, which demonstrated high levels of health literacy, with median responses ranging from 4–5 on a Likert scale with 5 corresponding to highest health literacy. Conclusion: Social determinants of health needs are prominent among patients who develop DKA, highlighting an opportunity for ED-based interventions to address specific SDoH factors to prevent the development of this disease. Self-reported health literacy scores were high in this patient population.